Human cis-acting elements regulating escape from X-chromosome inactivation function in mouse. (1st February 2018) - Peeters, Samantha B; Korecki, Andrea J; Simpson, Elizabeth M; Brown, Carolyn J
Abstract: A long-standing question concerning X-chromosome inactivation (XCI) has been how some genes avoid the otherwise stable chromosome-wide heterochromatinization of the inactive X chromosome. As 20% or more of human X-linked genes escape from inactivation, such genes are an important contributor to sex differences in gene expression. Although both human and mouse have genes that escape from XCI, more genes escape in humans than mice, with human escape genes often clustering in larger domains than the single escape genes of mouse. Mouse models offer a well-characterized and readily manipulated system in which to study XCI, but given the differences in genes that escape it is unclear whether the mechanism of escape gene regulation is conserved. To address conservation of the process and the potential to identify elements by modelling human escape gene regulation using mouse, we integrated a human and a mouse BAC each containing an escape gene and flanking subject genes at the mouse X-linked Hprt gene. Escape-level expression and corresponding low promoter DNA methylation of human genes RPS4X and CITED1 demonstrated that the mouse system is capable of recognizing human elements and therefore can be used as a model for further refinement of critical elements necessary for escape from XCI in humans.